Toward a Unified Analysis of the Brain Criticality Hypothesis: Reviewing Several Available Tools - Yu, Chaojun (Frontiers in Neural Circuits, 2022)
The study of the brain criticality hypothesis has been going on for about twenty years, various models and methods have been developed for probing this field, together with large amounts of controversial experimental findings. However, no standardized protocol of analysis has been established so far. Therefore, hoping to make some contributions to a standardization of such analysis, we review several available tools used for estimating the criticality of the brain in this paper.